2013
DOI: 10.1080/10401334.2013.842906
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Education: What Was, What Is, and What Will Be?

Abstract: Patient safety is an important topic that has been receiving more attention in the current health care climate. Patient safety as a curriculum topic in medical schools has only become apparent in the late 1990 s, and much more needs to be done. This article summarizes patient safety curricular content as it occurred (or did not occur) in medical education circles in the past (pre-1990 s), and present. It also makes some recommendations for the future of medical education curricula in the area of patient safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Analysis of the article content with the relevant categories "state", "health", and "education" shows that these publications are devoted to political (organizational and administrative), and police measures in the area of public security connected with health protection [13][14][15][16][17][18][19][20][21][22][23][24][25]; food security [26][27][28]; protection from threats and violence in educational sphere [29][30][31][32][33][34][35][36][37][38][39][40]; urban security [41][42][43][44][45][46][47]; and protection from crime and terrorism [48][49][50][51][52][53][54][55]. These life spheres and human behavior are evaluated for external risks and physical threats with preventive or reactive impacts on the environment and social relations being the factors and tools of protection from them.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the article content with the relevant categories "state", "health", and "education" shows that these publications are devoted to political (organizational and administrative), and police measures in the area of public security connected with health protection [13][14][15][16][17][18][19][20][21][22][23][24][25]; food security [26][27][28]; protection from threats and violence in educational sphere [29][30][31][32][33][34][35][36][37][38][39][40]; urban security [41][42][43][44][45][46][47]; and protection from crime and terrorism [48][49][50][51][52][53][54][55]. These life spheres and human behavior are evaluated for external risks and physical threats with preventive or reactive impacts on the environment and social relations being the factors and tools of protection from them.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that healthcare curricula should be redesigned from a patient safety perspective [ 7 , 8 ]. In particular, since nursing students are medical personnel who will enter the hospital field immediately after graduation and will be in charge of practical work through direct contact with patients, it is necessary to acquire the correct knowledge and attitudes about patient safety through the major curriculum [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consecuentemente, el principio Hipocrático de primum non nocere ha tomado revitalizada preponderancia en las últimas dos décadas. Comenzando con el reporte To Err is Human, publicado por el Instituto Americano de Medicina en 1999, la seguridad del paciente se ha convertido en la piedra angular de cualquier intervención médica, permeando a los currículo de pre y posgrado 3 . Se estima que los errores médicos prevenibles resultan en más de 400.000 muertes al año en EE.…”
Section: Introductionunclassified